Features of functioning and the role of integrated units in the AIC (Journal of Economic Research & Business Administration, 2017)
In modern conditions of particular relevance and importance of economicintegration has gained in the field of agriculture. The article examinesthe characteristics of integrated structures in agrarian and industrialcomplex, the role of agro-industrial integration as a source of real investment,improve the competitiveness of the form, the basis of the stabilizationand development of agriculture and related industries. In this regard,we identified linkages and relationship problems between adjacentmechanism of its branches involved in the process of product promotionfrom producer to consumer. Set out the organization of direction, purpose,structure integrated structures, comprising all members of the technologicalcycle of food production and its promotion to the end consumer, whichinclude agricultural producers, processors and service enterprises, trade.An effective mechanism for integrated structures in agrarian and industrialcomplex should provide an equivalent exchange between agriculture andindustry, the saturation of the food market at the expense of priority andeffective development of domestic production.